Analisis Pengkhianatan Kreatif dalam Puisi Terjemahan “The Wild Swans at Coole” Karya William Butler Yeats - Prihantono, Kahar Dwi (Jurnal Penerjemahan, 2019)
The treason in literary translation refers to translator’s subjective efforts to perform any deviation to eliminate any shackles of the language of the source text. Hence, the translated literary work is as close as possible to the characteristics of target readers. Creativity refers to any subjective performance of translator’s artistic scheme fulfilling his or her subjective intention. This article attempts to analyze the translation of William Butler Yeats’-an Irish poet who has won 1946 Nobel Prize in Literature- poem: "The Wild Swans at Coole" through the perspective of creative treason. in translation relating to aspects of personalized translation, omissions, abridged translation and trans-editing, relay translation, and adaptation. The study belongs to qualitative descriptive study and it applied creative treason approach as the core of mediotranslatology theory proposed by Tianzhen (2017). The result of the study proved that both poet-translators, Ikranagara and Asrowi, applied creative treason in several poem structures, namely typography, sound, diction, and rhetoric. The treasons carried out by both poet-translators covers three major categories, namely personalized translation-domestication, omissions, abridged translation which reflecs their individual styles. Keywords: “The Wild Swans at Coole”; William Butler Yeats; literary translation; creative treason, style